Heartlands of Eurasia: The Geopolitics of Political Space - Sengupta, Anita, (Lexington Books, 2009)
Heartlands of Eurasia explores how received metageographical knowledge informs the understanding of global processes and is subsequently transformed into geopolitical reasoning with foreign policy implications. It provides a detailed examination of writings, from both within the region and outside, that look into the significance of Halford Mackinder's heritage in the context of a vastly changed world situation. In particular, it attempts to examine how policy makers and strategic thinkers have used these geopolitical concepts as justification for their policy in the region. Finally, it attempts an analysis of the extent to which this policy thinking was translated into practice. While the study looks into how the vision of the 'pivotal' significance of a vast expanse of land finds its echoes in contemporary narratives, it also underlines the very creative ways in which Mackinder's ideas have been reinterpreted in keeping with the changing global dynamics. Making use of the way in which the region has been traditionally defined and the way in which the people defined themselves, the study brings into focus a debate on the usefulness of region or 'area'-based studies that are located in geographical imaginations. Anita Sengupta uses this connection to examine the following issues: geopolitical imaginations and their relevance in identifying 'areas' in the present context; the intersection between how areas are defined from an outsider perspective and how people define themselves; the extent to which these definitions have influenced policy; and the possibility or feasibility of the development of alternative geostrategic discourses. Mackinder himself did not specify the geographical area identified first as the 'pivot' and later the 'heartland,' but his ideas were focused on the 'closed heartland of Euro-Asia,' an area that was unassailable by sea power. This study therefore centers its debates around the Eurasian space in general, though the focus is on the Central Asian region and Uzbekistan in particular. The book is ideal for specialists working on the Eurasian region, graduate students interested in geopolitics as well as Eurasian and Central Asian studies, and undergraduates studying political science and international relations.